Liver Diseases in Pregnant Women, Principles of Treatment - Munira Khusainova Alisherovna; Zarrina Khaydarova Erkinovna; Suvon Yarmatov Tatlibayevich (Genius Journals, 2022)
This article is devoted to the problem of liver pathology in pregnant women. In the period from 2017-2021, 168 pregnant women with liver pathology were treated at the clinic. The pathological condition of the liver in pregnant women is characterized by a variety of etiological forms, variants of the course and prognosis. The article highlights cholestatic jaundice, acute fatty hepatosis of pregnant women, chronic hepatitis, cirrhosis of the liver. The results of treatment in pregnant women with liver pathology depend on the timing of admission of patients, the presence of complications, concomitant pathology, timely diagnosis and adequate surgical intervention, prolonged hepatotropic therapy.
Keywords: Cholestasis; Hepatitis; Cirrhosis Of The Liver In Pregnant Women; HELLP Syndrome